A retrospective study to determine correlation of physical activity with natural labor - Narahari, Padmavathi; Atluri, Anilasre (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Most pregnant women wish to have natural birth. Worldwide rate of caesarean is increasing due to various reasons. In this study we evaluate the correlation of physical activity with occurrence of normal delivery. Methods: This is a retrospective study on 200 women based on questionnaire regarding history of physical activity in primiparous women who had natural delivery or caesarean delivery. Sampling was done by purposive selective sampling method. All the women included in the study had delivered either by caesarean or natural birth with birth weight of the babies between 2.5-3.5 kg. Analysis was done by descriptive and inferential statistics. Results: Among 100 women with natural labor 83 had at least one or two kind of physical activity, whereas among 100 women with caesarean, only 12 had some kind of physical activity. Conclusions: Based on our findings inclusion of physical activity during antenatal period increased the rate of natural birth.